Refusal as Repair: Reflections on *Disorganising* - Amelia Wallin (Index Journal)
This article examines the relationship between art and crisis through a personal account of the *Disorganising* project initiated by West Space, Liquid Architecture, and Bus Projects in 2020. The article was written alongside the final stage of the *Disorganising* project, which coincided with the lifting of Melbourne's sixth and final lockdown and the "opening up" of Australia's states and territories. Drawing from the lived experience of the author, the opening section, "Living from Work," explores the experience of *Disorganising* during the pandemic. "Repair" situates *Disorganising* within a contradictory climate of crisis that tasks artists with economic recovery, and considers its possibilities as a reparative curatorial strategy. "Refuse" looks at examples that counter these expectations of recovery through the different modes of refusal practiced in *Disorganising*, including the refusal of productivity and competition; existing in contradiction; taking pause; exceeding timelines; being in duration; and working through the mess. The final section, "Return," considers what might happen next. By way of conclusion, this article considers "How to End *Disorganising*?" It reflects on the contradictions of the project and asks how one might evaluate projects of this nature.